Attitude of Farmers towards In-situ Water Conservation in Semi-Arid Regions of Tamil Nadu (Indian Journal of Extension Education, 2024)
Water scarcity poses a significant challenge for farmers in dryland regions. The availability of water in these dryland areas greatly impacts crop cultivation and directly affects the livelihoods of farmers. As a result, preserving water resources is crucial for achieving successful crop cultivation. Scientists emphasize that in-situ water conservation is more effective than other methods. However, previous research has indicated that farmers have been reluctant to adopt in-situ water conservation (ISWC) practices Therefore, this study was conducted to analyse dryland farmers’ attitude towards ISWC practices in the Pudukkottai district. The data was collected from 120 participants during September October 2023. Statistical analysis techniques, such as the correlation, regression, and path analysis, were used to analyze the data. The results indicate that a majority of the farmers (53.33%) displayed a highly favourable attitude towards in-situ water conservation. Furthermore, variables such as cropping intensity, innovativeness, information seeking behaviour, cosmopoliteness, risk orientation, scientific orientation, awareness of soil erosion problems and accessibility of farm implements were found to have a positive association with the attitude towards in-situ water conservation. The policy implications include providing incentives to farmers who adopt water conservation measures and implementing effective training programs.